An Enhanced Hybrid Method Using AES Algorithm And Arabic Text Steganography - Anes Abdulgahar Shaker
Cryptography and steganography are the most common methods for ciphering and hiding data, respectively. Cryptography is a technique uses mathematics to encrypt and decrypt data, where the data is converted into some other gibberish form, and then the encrypted data is transmitted. However, cryptography alone cannot guarantee that the data will be entirely secured because the scrambled message is still visible to the eavesdropper. On the other hand, steganography is the art and science of hiding conununication. Therefore, a stenographic system embeds hidden content in the unremarkable cover media such as text to avoid an eavesdropper's suspicion. Existing methods are still lacking in capacity and security. Hence, an enhanced hybrid method using existing Advanced Encryption Standard (AES) algorithm and new Arabic text steganography based on concept of lunar and solar letters is proposed. AES algorithm is chosen because symmetric encryption algorithm runs faster and performs better in smaller scale applications as compared to Asymmetric key algorithms. In addition, the memory requirement of Symmetric algorithm is lesser as compared to asymmetric. Five variations of text steganography methods namely Method A, Method B, Method C, Method D and Method E that consist of 28 Arabic letters classified into 14 solar letters and 14 lunar letters are proposed. Evaluation on capacity and security against three related existing methods were carried out. Capacity is evaluated using embedding ratio and efficiency ratio while security is evaluated using invisibility test. Invisibility test is carried out using a survey on random 100 Iraqi computer science students. Method A produces the highest embedding ratio 84.26% and the highest efficiency ratio 70.13%. In addition, method A produces the highest security with results of 100% from the invisibility survey when compared with four proposed and three existing methods. It is concluded that method A outweighs other methods in terms of capacity and security.